1916
DOI: 10.1021/i500011a006
|View full text |Cite
|
Sign up to set email alerts
|

The Nitration of Toluene to Trinitrotoluene

Abstract: Table 1-Analyses of OilsTable3-Rapid Hydrolysis of Linseed Oil Emulsions Analyses were made when oils were first obtained and 44 mos. later, at the time they were used in repainting tests. The oils were again analyzed 22 mos. later in September, 1916. Chemical changes occurring in the oils are denoted by the constants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is estimated that there are approximately 400 000 distillation columns in operation in the United States, which is about 90 % of all separation processes for product recovery and purification. [1] However, this process involves a large amount of heat to be supplied to the bottom reboiler, which is later removed from the top condenser. Mix et al [2] found that 60 % of the energy used by the chemical industry was for distillation.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there are approximately 400 000 distillation columns in operation in the United States, which is about 90 % of all separation processes for product recovery and purification. [1] However, this process involves a large amount of heat to be supplied to the bottom reboiler, which is later removed from the top condenser. Mix et al [2] found that 60 % of the energy used by the chemical industry was for distillation.…”
Section: Introductionmentioning
confidence: 99%
“…However, low fluxes and bulk rather than precise separations have limited its application up to now. 1 The separation of olefin-paraffin mixtures has been achieved using mainly glassy polymers because alkene permeability through these polymers is known to be higher than that of the corresponding alkane. 2 Elastic polymers show similar permeabilities for alkenes and alkanes.…”
Section: Introductionmentioning
confidence: 99%